Prevalence of Flexibility Among Health Care Professional Students: Life Sciences-Physiotheraphy - Shanmugananth, E.; kumaran, J. Muthu; M. Ranjani; K. Rekha; S. Vaishnavi; Nambi .S, Gopal (International Journal of Life Science and Pharma Research, 2023)
Flexibility is a physiological characteristic that allows an individual to execute voluntary movements of maximum joint angular amplitude within morphological limits, free of pain and restrictions. The prevention of musculoskeletal injuries and improvement in muscle movement and performance depend on body flexibility. The purpose of this study was to analyse the prevalence of flexibility among health care professional students. A total of 700 students, in which 68 students were excluded and 632 students were included, Subjects were assessed for joint flexibility by using the measurements of joint range of motion developed by Norkin and White. The inclusion and exclusion criteria were female students aged between 17 and 25 years with recent fractures and sprains, a history of neurological problems, and recent surgeries. The major muscles tested for flexibility are trapezius, pectoralis major, hip flexors, rectus femoris, hamstrings, and calf muscles, as these muscles commonly cause the restriction identified with stretching pain for each muscle. Statistical analyses were conducted according to gender, age, body mass index value[normal-overweight-obese], and the results of the muscle flexibility test. In the overall sample, 9.17% of students had pectoral muscle tightness; 22% of students had upper trapezius muscle tightness; 38% of students had hamstring muscle tightness; 18.2% of students had calf muscle tightness; 3.32% of students had adductor muscle tightness; and 9.33 % of students had rectus femoris muscle tightness. This study confirms that the flexibility of the major muscles is poor because of their daily activities, BMI, and ageing process. Poor flexibility may lead to poor posture and some musculoskeletal problems. These studies help them learn how important it is to do regular physical activities every day.